The Prescription of Chinese Herbal Medicine and Risk of Endometriosis in Women with Rheumatoid Arthritis: A Population-Based Cohort Study - Chen CJ; Livneh H; Chen WJ; Wang YH; Lu MC; Yeh CC; Yen CT; Tsai TY (Dove Medical Press, 2022)
Chia-Jung Chen,1 Hanoch Livneh,2 Wei-Jen Chen,1,3- 5 Yu-Han Wang,5 Ming-Chi Lu,6,7 Chia-Chou Yeh,1,4 Chieh-Tsung Yen,8 Tzung-Yi Tsai9- 11 1Department of Chinese Medicine, Dalin Tzu Chi Hospital, The Buddhist Tzu Chi Medical Foundation, Chiayi, Taiwan; 2Rehabilitation Counseling Program, Portland State University, Portland, OR, USA; 3Graduate Institute of Sports Science, National Taiwan Sport University, Taoyuan, Taiwan; 4School of Post-Baccalaureate Chinese Medicine, Tzu Chi University, Hualien, Taiwan; 5Center of Sports Medicine, Dalin Tzu Chi Hospital, The Buddhist Tzu Chi Medical Foundation, Chiayi, Taiwan; 6Division of Allergy, Immunology and Rheumatology, Dalin Tzu Chi Hospital, The Buddhist Tzu Chi Medical Foundation, Chiayi, Taiwan; 7School of Medicine, Tzu Chi University, Hualien, Taiwan; 8Department of Neurology, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Chiayi, Taiwan; 9Department of Nursing, Tzu Chi University of Science and Technology, Hualien, Taiwan; 10Department of Medical Research, Dalin Tzu Chi Hospital, The Buddhist Tzu Chi Medical Foundation, Chiayi, Taiwan; 11Department of Environmental and Occupational Health, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Chieh-Tsung Yen; Tzung-Yi Tsai, Tel +886-5-2648000-5003 ; +886-5-2648000-3209, Fax +886-5-2648006, Email dm335164@tzuchi.com.tw; dm732024@tzuchi.com.twPurpose: The systemic inflammation is believed to provide an outline of the association between rheumatoid arthritis (RA) and endometriosis. This retrospective cohort study aimed to explore the association of Chinese herbal medicine (CHM) use with the prevention of endometriosis onset in women diagnosed with RA.Methods: We utilized the claims data from the National Health Insurance of Taiwan from 2000 to 2009 and excluded individuals diagnosed with endometriosis before being diagnosed with RA, using age at clinical diagnosis. After selection and propensity-score matching, a total of 5992 females aged ≧20 years old and with newly diagnosed RA but without endometriosis at baseline were included, which contained 2996 CHM users and 2996 non-CHM users. All of them were followed until the end of 2013 to measure the incidence of endometriosis.Results: During the study period, we noticed that CHM users had a substantially lower incidence of endometriosis compared to non-CHM users (2.54 vs 5.19 per 1000 person-years). Use of CHM correlated significantly with a lower endometriosis likelihood even after adjusting for potential covariates, with the adjusted hazard ratio of 0.47 (95% confidence interval, 0.35- 0.65). A longer duration of CHM use was associated with a reduction in endometriosis risk, especially in those using CHM for more than 730 days. Uses of several herbal products may be associated with a lower risk of endometriosis, like Ge-Gen, Da-Huang, Huang-Qin, Ye-Jiao-Teng, Chuan-Niu-Xi, Shu-Jing-Huo-Xue-Tang, Du-Huo-Ji-Sheng-Tang, Ge-Gen-Tang, Shao-Yao-Gan-Cao-Tang, Ping-Wei-San, Gan-Lu-Yin, and Dang-Gui-Nian-Tong-Tang.Conclusion: Taken together, adding CHM to conventional therapy may reduce the incidence of endometriosis in women with RA. The therapeutic mechanisms and safety of these natural products may be a direction for future clinical studies.Keywords: endometriosis, rheumatoid arthritis, Chinese herbal medicines, propensity score match